The 2025 U.S. debt limit through the lens of financial markets - Luca Benzoni; Marisa Wernick (Federal Reserve Bank of Chicago, 2025)
We examine the 2025 U.S. debt limit episode through the lens of financial markets. First, we document an increase in trading activity in the U.S. sovereign CDS market, and we infer a probability of default from CDS premiums. We find that default risk reached 1% by the November 6 Presidential election, fell quickly after that, and progressively climbed back up in subsequent months to the current 1.1% level. Overall, these estimates are well below the default risk estimates for the debt-limit episodes of 2011, 2013, and 2023, which range from 4% to 6%. Second, so far we only find small distortions in the market for Treasury bills that mature around the "X-date," when Treasury is expected to extinguish its existing resources, and thus would be most affected by a hypothetical default. This is in contrast with the 2023 episode, when bills maturing around the X-date traded with a yield that was about 1% higher than those maturing in other months. Third, we discuss the broader consequences that debt-limit events can have for the level of bank reserves at the Federal Reserve, and their implications for money markets liquidity.
Keywords: G10; G12; G18; G28; E32; E43; E44; 330; default; sovereign CDS; default probabilities; U.S; CDS; debt limit